2021
DOI: 10.1016/j.psj.2021.101224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dicopper oxide and copper sulfate on growth performance and gut microbiota in broilers

Abstract: An experiment was conducted to determine the effects of two sources of copper ( Cu ) from copper sulfate ( CuSO 4 ) and dicopper oxide ( Cu 2 O , CoRouge) at three levels of inclusion (15, 75, and 150 mg/kg) on growth performance and gut microbiota of broilers. A total of 840 one-d-old male chickens (Ross 308) were weighed and randomly allocated to seven dietary treatments: negative control ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 89 publications
(103 reference statements)
3
16
0
Order By: Relevance
“…The observation that Cu 2 O seemed to be more efficient than CuSO 4 in terms of reducing the growth of Rikenellaceae family and Holdemanella genus may indicate that Cu 2 O promotes intestinal health to a greater degree than CuSO 4 . Similar observations were reported from a study with broiler chickens ( Forouzandeh et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The observation that Cu 2 O seemed to be more efficient than CuSO 4 in terms of reducing the growth of Rikenellaceae family and Holdemanella genus may indicate that Cu 2 O promotes intestinal health to a greater degree than CuSO 4 . Similar observations were reported from a study with broiler chickens ( Forouzandeh et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Therapeutic levels of Cu alter the intestinal microbiota in poultry ( Pang et al, 2009 ; Forouzandeh et al, 2021 ) and swine ( Wang et al, 2012 ; Villagómez-Estrada et al, 2020 ). Copper supplementation may act by reducing the total pathogenic organism in the gut ( Xia et al, 2004 ) and reducing susceptibility to disease due to its antimicrobial effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 16 mg/kg of supplemental Cu in both IN-Cu and HME-Cu tended to increase the BWG at phase 2. In accordance with previous study, supplementation of 15 mg/kg Cu, CuSO 4 , or Cu 2 O, had tendance increasing the average daily gain of broilers [ 38 ]. In addition, Wang et al [ 39 ] reported that 50 mg/kg nano-Cu supplementation in diets increased the BWG in broiler chickens.…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that supplementation with 16 mg/kg of Cu tended to decrease E. coli population in cecum. In contrast, 150 mg/kg of CuSO 4 in diets decreased the abundance of Streptococcaceae and Corynebacteriaceae, Gram-positive bacteria, in ileum [ 38 ]. Furthermore, Wang et al [ 39 ] reported that supplementation with 100 mg/kg of copper-loaded chitosan nanoparticles in broiler diets not only increased the Lactobacillus and Bifidobacterium populations in cecum but also decreased the E. coli population compared to the control.…”
Section: Discussionmentioning
confidence: 99%